The Impact of Motivation and Collaborative Learning on Academic Achievement - Anggeraini, Yentri; Nilawijaya, Rita (Jurnal Pendidikan Progresif, 2021)
Abstract: The Impact of Motivation and Collaborative Learning on Academic Achievement. Objective: This article aimed at explaining the impact of motivation in learning English and the application of collaborative learning on English learning achievement. Method: A three by two factorial design was employed and the sample of this research was 48 students of English for Special Purposes (ESP) subject. The valid and reliable motivation questionnaire and English test were distributed to gather the data and were analyzed by independent simple t-test and two-way ANOVA. Result: The result presented that there was a significant interaction between motivation and the application of collaborative learning to the ESP learners‘ English achievements with the sig. 0.00. Conclusion: It can be derived that the motivation and the use of collaborative learning gave a positive impact on ESP learners‘ English achievement and there was a significant interaction between learning English motivation and the application of collaborative learning to the ESP learners‘ English achievements. Keywords: Motivation, collaborative learning, academic achievement. DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202108